La gestión crediticia y su impacto en el desarrollo socioeconómico de los socios de la Caja Solidaria Nueva Esperanza, de la comunidad de Casipamba, parroquia Gabriel Ignacio de Veintimilla, catón Guaranda, Provincia Bolívar, en el año 2017. - Gaglay Faz, Jessica Verónica (2017)
Once the academic activities of the Accountancy and Audit department and the School of Business Management were completed, we had a pending investigation work prior to obtaining a professional degree in our beloved State University of Bolívar. Community solidarity funds have not only become a form of savings and credit, but also expand and go beyond the aspirations of those who comprise it, most of which are women who are highly organized and based on the principle of trust has allowed them to move forward. Faced with this requirement and after a series of analyzes, we are inclined to do this research work in the area of solidarity funds, and this is how being native of this province and interested in giving guidelines for solving the series of problems that afflict its inhabitants decided to focus on the Solidarity Fund of the Community of Casipamba Ignacio de Veintimilla Parish to investigate, analyze and suggest mechanisms for optimal functioning in the aforementioned sector. Throug h this research work, it is vitally important to highlight the influence of credit management in solidarity funds in the socioeconomic development of the inhabitants of the rural sector in different parts of the community that help in the opening and socioeconomic growth , as agriculture, livestock that impact on the development of the partners, based on their skills and abilities. For what can be concluded as a result of the present work that the existence and functioning of solidarity funds in the province and in this community have been very beneficial for the development of said people, remaining to improve certain processes in granting credits and in the resection of horros looking for ways to transform them into more agile and dynamic for the attention and immediate solution of the needs of their associates.